Estimation of biogenic contamination of surface reservoirs of Poltava region - Степова, О. В.; Рома, В. В. (Scientific Progress & Innovations, 2016)
The ecological estimation of the state of river waters is described in the article. The analysis of the last researches and publications consisting of the ecological state of the river systems of Poltava region is given in the article. We investigated dynamics of maintenance of biogenic elements in the surface objects of Poltava region. We did the analysis of problems of eutrophication of surface reservoirs at regional level. We have suggested a list of basic measures in relation to limitation of the use of cleansers, timely control of cleansing equipment, its modernization, and orientation on the European quality norms which will allow to regulate and control the hit of phosphates with flow waters to the surface reservoirs.